CONTROLLING RISK DUE TO NOISE ON FERRY BOAT - Aleksandar Nikolic (Promet (Zagreb), 2013)
Environmental and occupational noise is common nuisance that affects the health of employees. Performed health checks of employees engaged by Company “Pomorski Saobraćaj” showed that 5% of examined sailors had hearing loss. The results were a trigger for starting experiment on noise risk assessment with objective to discover possibilities of noise pollution presence, precise significant noise sources and describe solutions for eliminating negative effects. Several measurements on five positions were performed on ferry boat “KAMENARI”, according to EC Physical Agents Directive and Merchant Shipping and Fishing Vessels Regulations 2007. Noise on selected positions exceeded the limit for about 1-5dB. Noise exposure level was 84.5dB. Diesel engine, exhaust system and structural noise were main sources of excessive noise. Experiment shows noise presence as nuisance that affects sailors. Noise presents a serious threat for sailor’s health. It interferes with crew communication and jeopardizes navigation safety. Technical measures, crew health checks and noise monitoring could prevent all negative effects.